RETRACTED: Effect of Intraoperative Ventilation Strategies on Postoperative Pulmonary Complications: A Meta-Analysis - Lei, Min; Bao, Qi; Luo, Huanyu; Huang, Pengfei; Xie, Junran (Frontiers in Surgery, 2021)
Introduction The role of the intraoperative ventilation strategies in subjects undergoing surgery is still conflicting. This meta-analysis study was performed to assess the relationship between low tidal volumes strategy and conventional mechanical ventilation in subjects undergoing surgery. Methods Through a systematic literature search up to December 2020, 28 studies included 11846 subjects undergoing surgery at baseline and reported a total of 2638 receiving low tidal volumes strategy and 3632 receiving conventional mechanical ventilation, were found recording relationships between low tidal volumes strategy and conventional mechanical ventilation in subjects undergoing surgery. Odds ratio (OR) or mean difference (MD) with 95% confidence intervals (CIs) was calculated between low tidal volumes strategy versus conventional mechanical ventilation using the dichotomous and continuous methods with a random or fixed-effect model. Results Low tidal volumes strategy during surgery was significantly related to lower rate of postoperative pulmonary complications (OR, 0.60; 95% CI, 0.44-0.83, p<0.001), aspiration pneumonitis (OR, 0.63; 95% CI, 0.46-0.86, p<0.001), and pleural effusion (OR, 0.72; 95% CI, 0.56-0.92, p<0.001) compared to conventional mechanical ventilation. However, low tidal volumes strategy during surgery was not significantly correlated with length of hospital stay (MD, -0.48; 95% CI, -0.99-0.02, p=0.06), short-term mortality (OR, 0.88; 95% CI, 0.70-1.10, p=0.25), atelectasis (OR, 0.76; 95% CI, 0.57-1.01, p=0.06), acute respiratory distress (OR, 1.06; 95% CI, 0.67-1.66, p=0.81), pneumothorax (OR, 1.37; 95% CI, 0.88-2.15, p=0.17), pulmonary edema (OR, 0.70; 95% CI, 0.38-1.26, p=0.23), and pulmonary embolism (OR, 0.65; 95% CI, 0.26-1.60, p=0.35) compared to conventional mechanical ventilation. Conclusions Low tidal volumes strategy during surgery may have an independent relationship with lower postoperative pulmonary complications, aspiration pneumonitis, and pleural effusion compared to conventional mechanical ventilation. This relationship encouraged us to recommend low tidal volumes strategy during surgery to avoid any possible complications.